Menguji Ketercapaian Syarat-syarat Hadis Mutawatir (Kritik atas Temuan G.H.A. Juynboll) - Abdul Hakim Wahid (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2022)
This article aims to test the achievement of the requirements for mutawatir hadiths, which according to Juynboll’s view, in general, mutawatir transmissions will not be found in the Prophet's hadiths. He said that mutawatir hadith only occurred in a limited number of cases with non-standard and not clearly structured criteria, and if all hadith transmitters were presented individually, then they could not be included in the mutawatir criteria. This article uses a qualitative method with data sources throughout the canonical and pre-canonical hadith books. After an in-depth study of all the transmission lines, this article concludes that what Juynboll concluded was incorrect. This article found that the hadith about washing the khuffayn qualifies as a mutawatir hadith as required by Ibn Hajar.